Effect of Displacement on Social and Economic Positions, Case Study Displaced Households in Gadaref, Sudan 2023 - Fayga Hussien Ballal Awad, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
The study aimed at Discovering the socio-economic impacts of armed conflict on displaced household in Gadaref; Sudan. problem of the study has acted in the coming question: what are the effects of Displacement on Social and Economic Positions, in displaced households in Gadaref; Sudan, the study followed the descriptive analytical approach (the survey method). The study achieved to; displacement has significant effects on food resources availability, financial transfers from the relatives, income, received assistance as food, cure, Beds. In addition to other income source as loan, homes and properties' affection, type of residence, and basic services at residence.